The handbook of global science, technology, and innovation - Archibugi, Daniele; Filippetti, Andrea, 1977- (Chichester, West Sussex, UK : John Wiley & Sons Inc., 2015)
'Provides a state-of-the-art overview of science, technology, and innovation in the context of globalization and global policy'--
Editors' introduction: science, technology, and innovation go global / Daniele Archibugi and Andrea Filippetti -- Part I. Global trends. 1. The convergence paradox: the global evolution of national innovation systems / Fulvio Castellacci and Jose Miguel Natera ; 2. World top university rankings: from distribution to implications on national knowledge creation and competitiveness / Thanh Quang Le and Kam Ki Tang ; 3. The international race of top supercomputers and its implications / Kam Ki Tang and Thanh Quang Le ; 4. Changes in product aesthetics: an omitted dimension in economic analyses of innovation activities / Paul Stoneman ; 5. Is the world of science moving to the East?: what bibliometrics says / Ping Zhou and Jiang Li -- Part II. The globalization of technology and innovation. 6. Innovation, internationalization, and the transnational corporation / Grazia Ietto Gillies ; 7. International R & D alliances by firms: origins and development / Rajneesh Narula and Andrea Martinez Noya ; 8. The globalization of knowledge-intensive services / Ian Miles and Marcela Miozzo ; 9 Capital and technology flows: changing technology acquisition strategies in developing countries / Suma Athreye and Sandeep Kapur ; 10. Clusters and global innovation: the role of connectedness and connectivity / Mark Lorenzen and Ram Mudambi ; 11. New product development in emerging economies: innovation in reverse from China / Simone Corsi, Alberto Di Minin, and Andrea Piccaluga ; 12. Crowdfunding: toward the democratization of innovation financing / Alessandro Cordova, Johanna Dolci, and Gianfranco Gianfrate -- Part III. Spaces and flows of knowledge. 13. Harnessing the geography of innovation: toward evidence-based economic development policy / Maryann P. Feldman and Jongmin Choi ; 14. MNE innovation networks and the role of cities / Simona Iammarino and Philip McCann ; 15. The rise of the global creative class / Richard Florida and Charlotta Mellander ; 16. Global science collaboration / Stefan Hennemann and Ingo Liefner ; 17. International mobility of scientists / Kieron Flanagan ; 18. The role of global connectedness in the development of indigenous science in middle-income countries / Helena Barnard, Robin Cowan, Marta Fernandez de Arroyabe Arranz, and Moritz Muller ; 19. Global trends in brain drain and likely scenario in the coming years / Alessio Terzi -- Part IV. Global institutions and intellectual property rights. 20. The globalization of intellectual property rights / Andrea Filippetti and Daniele Archibugi ; 21. Patents, monopoly power, and the pricing of pharmaceuticals in low-income nations / F.M. Scherer ; 22. Global governance and intangible cultural heritage in the information society: at the crossroads of IPRs and innovation / Paolo Davide Farah and Riccardo Tremolada -- Part V. The global governance of science and technology. 23. Knowledge as global public good / Daniele Archibugi and Andrea Filippetti ; 24. From governmental open data toward governmental open innovation (GOI): a global perspective / Sabine Brunswicker and Jeremiah Johnson ; 25. Serendipity and chance in scientific discovery: policy implications for global society / Donald Gillies ; 26. Global climate change and the direction of technological change / Andrew Tylecote ; 27. Global risks: cause and consequence of the new interactions between science, technology, and society / Jean-Yves Heurtebise ; 28. Globalization, regionalization, and technological change / Frederick Guy -- Index.
Machine generated contents note: Notes on Contributors viii Editors' Introduction: Science, Technology, and Innovation Go Global 1 Daniele Archibugi and Andrea Filippetti Part I Global Trends 13 1 The Convergence Paradox: The Global Evolution of National Innovation Systems 15 Fulvio Castellacci and Jose Miguel Natera 2 World Top University Rankings: From Distribution to Implications on National Knowledge Creation and Competitiveness 46 Thanh Quang Le and Kam Ki Tang 3 The International Race of Top Supercomputers and Its Implications 69 Kam Ki Tang and Thanh Quang Le 4 Changes in Product Aesthetics: An Omitted Dimension in Economic Analyses of Innovation Activities 88 Paul Stoneman 5 Is the World of Science Moving to the East?: What Bibliometrics Says 113 Ping Zhou and Jiang Li Part II The Globalization of Technology and Innovation 129 6 Innovation, Internationalization, and the Transnational Corporation 131 Grazia Ietto?]Gillies 7 International R & D Alliances by Firms: Origins and Development 148 Rajneesh Narula and Andrea Martinez?]Noya 8 The Globalization of Knowledge?]Intensive Services 175 Ian Miles and Marcela Miozzo 9 Capital and Technology Flows: Changing Technology Acquisition Strategies in Developing Countries 195 Suma Athreye and Sandeep Kapur 10 Clusters and Global Innovation: The Role of Connectedness and Connectivity 216 Mark Lorenzen and Ram Mudambi 11 New Product Development in Emerging Economies: Innovation in Reverse from China 232 Simone Corsi, Alberto Di Minin, and Andrea Piccaluga 12 Crowdfunding: Toward the Democratization of Innovation Financing 249 Alessandro Cordova, Johanna Dolci, and Gianfranco Gianfrate Part III Spaces and Flows of Knowledge 271 13 Harnessing the Geography of Innovation: Toward Evidence?]Based Economic Development Policy 273 Maryann P. Feldman and Jongmin Choi 14 MNE Innovation Networks and the Role of Cities 294 Simona Iammarino and Philip McCann 15 The Rise of the Global Creative Class 317 Richard Florida and Charlotta Mellander 16 Global Science Collaboration 347 Stefan Hennemann and Ingo Liefner 17 International Mobility of Scientists 368 Kieron Flanagan 18 The Role of Global Connectedness in the Development of Indigenous Science in Middle?]Income Countries 386 Helena Barnard, Robin Cowan, Marta Fernandez de Arroyabe Arranz, and Moritz Muller 19 Global Trends in Brain Drain and Likely Scenario in the Coming Years 411 Alessio Terzi Part IV Global Institutions and Intellectual Property Rights 423 20 The Globalization of Intellectual Property Rights 425 Andrea Filippetti and Daniele Archibugi 21 Patents, Monopoly Power, and the Pricing of Pharmaceuticals in Low?]Income Nations 447 F.M. Scherer 22 Global Governance and Intangible Cultural Heritage in the Information Society: At the Crossroads of IPRs and Innovation 462 Paolo Davide Farah and Riccardo Tremolada Part V The Global Governance of Science and Technology 481 23 Knowledge as Global Public Good 483 Daniele Archibugi and Andrea Filippetti 24 From Governmental Open Data Toward Governmental Open Innovation (GOI): A Global Perspective 508 Sabine Brunswicker and Jeremiah Johnson 25 Serendipity and Chance in Scientific Discovery: Policy Implications for Global Society 529 Donald Gillies 26 Global Climate Change and the Direction of Technological Change 544 Andrew Tylecote 27 Global Risks: Cause and Consequence of the New Interactions Between Science, Technology, and Society 562 Jean?]Yves Heurtebise 28 Globalization, Regionalization, and Technological Change 579 Frederick Guy Index 000.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Research, Industrial -- Handbooks, manuals, etc; Technology transfer -- Handbooks, manuals, etc; Technology and state -- Handbooks, manuals, etc; Science and state -- Handbooks, manuals, etc; Research, Industrial -- Handbooks, manuals, etc; Electronic books; Handbooks and manuals; Electronic books